Analisis Peluang Dan Tantangan Koperasi Desa Merah Putih Dalam Pemberdayaan Ekonomi Desa - Syafrizal, Rodi; Aulia, Cindi; Hasyim, Liza Widya (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
Rural-urban inequality remains a structural problem in national economic development. This disparity is characterized by low rural income, limited infrastructure, and weak human resource capacity. The